ANALYSIS OF THE IMPLEMENTATION OF THE RTRW LOCAL REGULATION IN COASTAL BOUNDARY PROTECTION - Febriyanti, Diyah Anggun; Ramli, Asmarani (Law Research Review Quarterly, 2025)
Settlement development in the coastal area of Sendangmulyo Village has significant environmental and socioeconomic impacts. This research analyzes the impact of development as well as constraints in the implementation of the Rembang Regency RTRW Regulation 2023-2043 related to coastal boundary protection. A qualitative approach was used with data collection techniques in the form of interviews, observations and document studies. Data analysis was conducted using content analysis. The results showed that settlement development causes damage to coastal ecosystems, such as loss of natural vegetation and increased risk of abrasion and tidal flooding. Socio-economically, this development triggers conflicts between economic interests and environmental preservation, and shows low public awareness of coastal ecosystem protection. In the implementation of the Rembang Regency RTRW regulation 2023-2043, three main obstacles were found: lack of supervision, lack of public awareness, and weak coordination between related parties. This research found that weak inter-agency coordination is a major factor in the ineffectiveness of the coastal boundary protection policy, an aspect that has not been studied much before. Conflicts of economic and environmental interests in Sendangmulyo Village are also more complex compared to other areas due to the lack of community understanding of the applicable regulations. This research contributes to uncovering the specific impacts of residential development on coastal ecosystems after the implementation of the 2023-2043 Regional Spatial Planning Regulation. Protection of riparian areas requires strengthening regulatory oversight, continuous community education, and increased cross-sectoral coordination to optimize the implementation of the Rembang Regency RTRW 2023-2043.